STATE FAILURE AS A FACTOR IN INTERNATIONAL GLOBAL COUNTERACTING OPERATIONS: NETWORK MODELING - Tikhomirov, A.; Trufanov, A.; Caruso, A.; Rossodivita, А.; Umerov, R.; Umerova, Z. (Journal of Information Technologies in Education (ITE), 2012)
In the paper are considered the need for build cooperation and collaboration among all entities and actors. Comprehensive Network Lace is based on an end-to-end description of major categories of interactions for sets of entities using a multilayer (multi-level) variety of complex networks.